Significance of Lipid Fatty Acid Composition for Resistance to Winter Conditions in Asplenium scolopendrium - Alexander Voronkov; Tatiana Ivanova (Biology, 2022)
Ferns are one of the oldest land plants. Among them, there are species that, during the course of evolution, have adapted to living in temperate climates and under winter conditions. Asplenium scolopendrium is one such species whose fronds are able to tolerate low subzero temperatures in winter. It is known that the resistance of ferns to freezing is associated with their prevention of desiccation via unique properties of the xylem and effective photoprotective mechanisms. In this work, the composition of A. scolopendrium lipid fatty acids (FAs) at different times of the year was studied by gas–liquid chromatography with mass spectrometry to determine their role in the resistance of this species to low temperatures. During the growing season, the polyunsaturated FA content increased significantly. This led to increases in the unsaturation and double-bond indices by winter. In addition, after emergence from snow, medium-chain FAs were found in the fronds. Thus, it can be speculated that the FA composition plays an important role in the adaptation of A. scolopendrium to growing conditions and preparation for successful wintering.